Technical Criteria for designating efficacy trial Centers –East African Community (EAC) - EAC (EAC, 2019)
This document prescribes the technical requirements for private or public institutions for designation as Efficacy Trial Centers for conducting efficacy studies that support or are intended to support applications for registration of pesticides in the East African Community (EAC). It is intended to ensure the quality and integrity of efficacy study results that are submitted to the EAC or its Partner States in support of pesticides registration or an extension of uses.
Keywords: Aflatoxin; Regional agriculture